2011
DOI: 10.5897/ajb11.2171
|View full text |Cite
|
Sign up to set email alerts
|

Mineral content of the rocket plant (Eruca sativa)

Abstract: Rocket (Eruca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Wu et al (2007), studying the tolerance of 158 materials from Brassica rapa L. at high concentrations of Zn, reported a low correlation between leaf iron and zinc contents in plants moderately and highly tolerant to the micronutrient. Neriman et al (2011), carrying out the nutritional characterization of 30 arugula samples from different locations, did not verify correlation between zinc and iron contents in the leaf. On the other hand, it is noted that with the highest dose of applied zinc, no Fe deficiency was observed, a factor that would also explain the lack of effect on chlorophyll a and b contents, since, according to Ebbs & Uchil (2008), iron deficiency due to high doses of Zn is one of the causes of the decrease in chlorophyll values.…”
Section: Discussionmentioning
confidence: 93%
“…Wu et al (2007), studying the tolerance of 158 materials from Brassica rapa L. at high concentrations of Zn, reported a low correlation between leaf iron and zinc contents in plants moderately and highly tolerant to the micronutrient. Neriman et al (2011), carrying out the nutritional characterization of 30 arugula samples from different locations, did not verify correlation between zinc and iron contents in the leaf. On the other hand, it is noted that with the highest dose of applied zinc, no Fe deficiency was observed, a factor that would also explain the lack of effect on chlorophyll a and b contents, since, according to Ebbs & Uchil (2008), iron deficiency due to high doses of Zn is one of the causes of the decrease in chlorophyll values.…”
Section: Discussionmentioning
confidence: 93%
“…As a result, it has been reported that the evaluation of mineral content in plants is extremely important because the high mineral content of herbal products provides significant benefits in terms of human nutrition and health (Grusak & Dellapenna, 1999). Most of the macro (P, Ca and K) and micro elements (Fe, Zn, Mn) of our Rocket samples were higher than the results of Haag & Minami (1988), Hussain et al (2013), Barlas et al (2011) and Matev et al (2018). These differences may possibly be due to factors such as cultivar, growing conditions, plant nutrient content of the soil and irrigation.…”
Section: Resultsmentioning
confidence: 70%
“…In addition, it can be said that rocket is a good source of K, Ca, P and Mg, although the mineral contents of rocket partially decrease with drying. Barlas et al (2011) assessed 4.32% N, 0.25% P, 5.13% K, 2.95% Ca, 0.58% Mg,799.88 Na,350 Fe,5.36 Cu,40.58 Mn and 64.86 mg kg À1 Zn in rocket (E. sativa) leaves. Also, Haag & Minami (1988) found between 37 and 41 mg/100 g Mg in rocket leaves, while Bianco (1995) (Tripodi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations